Analysis of the Influence of Cost Management, Operational Efficiency, Service Innovation, and Customer Loyalty on Return on Assets (ROA) in Star-Rated Hotels in Jakarta - Renny Yulia Bahren; Erico Indra Martha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of Cost Management, Operational Efficiency, Service Innovation, and Customer Loyalty on Return on Assets (ROA) in star-rated hotels located in Jakarta. A quantitative research approach was employed, with data collected through questionnaires distributed to managers, supervisors, and finance and operational staff of three- to five-star hotels in Jakarta. Data were analyzed using SPSS version 26.0, through validity and reliability testing, classical assumption testing, and multiple linear regression analysis. The results indicate that all independent variables have a significant and positive influence on ROA. Among them, Customer Loyalty exerts the strongest effect, followed by Service Innovation, Operational Efficiency, and Cost Management. These findings suggest that the profitability of hotel assets is not only driven by financial control but also by the ability to maintain customer relationships and implement continuous innovation. Thus, achieving optimal ROA requires an integrated managerial approach that balances internal efficiency with customer-oriented service innovation